Short-term effects of argon cold atmospheric plasma on canine corneas ex vivo - Dick, Juliane; Lockow, Sandra; Baumgärtner, Wolfgang; Volk, Holger Andreas; Busse, Claudia (Frontiers in Veterinary Science, 2025)
PurposeTo analyse the effects of argon cold atmospheric plasma (CAP) on canine corneas.MethodsHealthy canine eyes (n = 20) were subjected to a keratectomy (5 × 7 mm, 400 μm) and divided into two control (c1—not cultured; t0—cultured) and two treatment groups (t2, t5—treatment of 2 or 5 min, cultured); n = 5 eyes each. The kINPen® VET (neoplas GmbH, Greifswald, Germany) was used for CAP treatment. Corneas (t0, t2, t5) were cultured at an air-liquid interface (72 h). Histopathological and immunohistochemical (Ki-67, Caspase-3, α-SMA) examinations were performed.ResultsCorneal epithelization was complete and epithelial thickness was similar in all eyes. The number of perilimbal epithelial cell nuclei varied between groups with c1 = 22 ± 6, t0 = 13 ± 5, t2 = 15 ± 5 and t5 = 10 ± 4 nuclei/randomized fields and was lowest in t5, which was significantly different from t2 but not from t0. Ki-67 positive cells in the stroma varied between groups with c1 = 0.2 ± 0.45, t0 = 8 ± 12, t2 = 18 ± 12 and t5 = 10 ± 7 positive cells/section. More Ki-67 positive cells were found in t2 compared to t5. This was not significantly different from t0. Caspase-3 and α-SMA expression were similar in all treatment groups.ConclusionCanine corneas treated with CAP showed similar corneal wound healing compared to untreated corneas ex vivo. A 5-min CAP application results in a lower perilimbal epithelial cell density and fewer Ki67 positive stromal cells compared to the 2-min treatment.